Obcokrajowcy studiujący w Polsce w okresie międzywojennym w dokumentach Ministerstwa Wyznań Religijnych i Oświecenia Publicznego - Kula, Ewa; Pękowska, Marzena (Biuletyn Historii Wychowania, 2020)
After regaining independence, in 1918–1939 there was a rapid development of scientific culture in Poland. The aim was to recreate the network of Polish scientific institutions, to create new centers from scratch and to increase the number of scientific staff. Efforts were also made to include the Polish scientific community in world science. Cultural relations with other countries were maintained, inter alia, by implementing the provisions and conventions on intellectual cooperation signed by Poland with other countries. These documents also included issues related to teaching. The aim of the presented study is to show students’ scholarship exchange, first of all granting scholarships to foreign students during the interwar period by the Ministry of Religious Affairs and Public Education. The basis of the research are mainly archival sources concerning the initiation and support of scholarship activities, collected in Central Archives of Modern Records in Warsaw. Analysis of the sources made it possible to develop a preliminary chara-cterization of these initiatives.